RADIKALISME, FUNDAMENTALISME ISLAM MASA KINI - Iqbal, Muhammad; ., Baharuddin (Universitas Islam Negeri Alauddin Makassar, 2023)
Fundamentalists are one of the streams that do not want to accept change in the sense that they are against reform. So, they are careful to emphasize that the announcement of the prophethood of Muhammad is not something new, but only continues the series of prophets and apostles who preceded him. Meanwhile, radicalism is a group that is often viewed by the West as a terrorist which aims to undermine political authority by means of jihad. That is, these radical religious movements make jihad as a method to achieve their goals, namely the order of the Islamic system (al-nizām al-Islāmi). In addition, radicals are considered narrow-minded, ultra zeolous, or want to achieve goals by using violent means. Because it is understandable why most Muslim scholars view radicalism as an unfavorable term and cause misunderstanding. This view is also found in Western orientalists and scholars who understand Islam.